Virtual and Reality: A Neurophysiological Pilot Study of the Sarcophagus of the Spouses - Andrea Giorgi; Stefano Menicocci; Maurizio Forte; Vincenza Ferrara; Marco Mingione; Pierfrancesco Alaimo Di Loro; Bianca Maria Serena Inguscio; Silvia Ferrara; Fabio Babiloni; Alessia Vozzi; Vincenzo Ronca; Giulia Cartocci (Brain Sciences, 2023)
Art experience is not solely the observation of artistic objects, but great relevance is also placed on the environment in which the art experience takes place, often in museums and galleries. Interestingly, in the last few years, the introduction of some forms of virtual reality (VR) in museum contexts has been increasing. This has solicited enormous research interest in investigating any eventual differences between looking at the same artifact either in a real context (e.g. a museum) and in VR. To address such a target, a neuroaesthetic study was performed in which electroencephalography (EEG) and autonomic signals (heart rate and skin conductance) were recorded during the observation of the Etruscan artifact “Sarcophagus of the Spouses”, both in the museum and in a VR reproduction. Results from EEG analysis showed a higher level of the Workload Index during observation in the museum compared to VR (p = 0.04), while the Approach–Withdrawal Index highlighted increased levels during the observation in VR compared to the observation in the museum (p = 0.03). Concerning autonomic indices, the museum elicited a higher Emotional Index response than the VR (p = 0.03). Overall, preliminary results suggest a higher engagement potential of the museum compared to VR, although VR could also favour higher embodiment than the museum.